Effects of Short-Acting Opioids on Intraocular Pressure during General Anesthesia: Systematic Review and Network Meta-Analysis - Jian-You Huang; Ping-Cheng Shih; Chu-Ting Chen; Han-Yu Lin; Yung-Jiun Chien; Meng-Yu Wu; Chih-Hao Chen; Chun-Yu Chang (MDPI AG, 2022)
Intraocular pressure (IOP) is crucial to the well-being of eyes. During anesthesia, the administration of succinylcholine and endotracheal intubation are associated with an increase in IOP, which may be attenuated by short-acting opioids. However, the drug of choice among the commonly used short-acting opioids is unclear. This study aimed to evaluate the effects of fentanyl, sufentanil, alfentanil, and remifentanil on IOP measured after the administration of succinylcholine and after endotracheal intubation in patients undergoing general anesthesia. Five databases were searched. Randomized controlled trials (RCTs) that compared short-acting opioids and reported at least one of the clinical outcomes of interest were included. Nine RCTs with 357 patients were included. Remifentanil (1 μg kg−1) more effectively alleviated the increase in IOP than the placebo after the administration of succinylcholine [mean difference (MD) of IOP, −3.64; confidence interval (CI), −5.47 to −1.81 and after endotracheal intubation (MD, −9.71; CI, −11.91 to −7.51). Remifentanil (1 μg kg−1) ranked the best in terms of both attenuating the increase in IOP after the administration of succinylcholine [surface under the cumulative ranking curve (SUCRA), 0.91; normalized entropy (NE), 0.47; and after endotracheal intubation (SUCRA, 0.89; NE, 0.54) among all of the treatments. Remifentanil (1 μg kg−1) should be considered the drug of choice in the circumstances where increased IOP is a great concern.